An induced pluripotent stem cell line (SDQLCHi033-A) derived from a patient with maple syrup urine disease type Ib carrying a homozygous mutation in BCKDHB gene - Bin Wang; Chen Liu; Haiyan Zhang; Zhongtao Gai; Yi Liu (Stem Cell Research, 2021)
Maple syrup urine disease (MSUD) type Ib is a subclass of MSUD (248600) which is an inborn error of metabolism caused by defects in the branched-chain α-ketoacid dehydrogenase complex. An induced pluripotent stem cell (iPSC) line was generated from an 11-day-old girl diagnosed with maple syrup urine disease type Ib and carrying a novel homozygous mutation of c.1097C>A (p.P366Q) in BCKDHB gene. This cell line demonstrates a normal karyotype and maintains a pluripotent state, displaying the capability to differentiate into the three germ layer lineages and the absence of exogenous pluripotency vector expression.